Yield stability and adaptability of newly selected black rice mutant lines (Oryza sativa) across dry-season agroecosystems in Central Java, Indonesia - AHMAD SOFIAN; EDI PURWANTO; SUTARNO SUTARNO; PARJANTO PARJANTO (Society for Indonesian Biodiversity, 2026)
Abstract. Sofian A, Purwanto E, Sutarno, Parjanto. 2026. Yield stability and adaptability of newly selected black rice mutant lines (Oryza sativa) across dry-season agroecosystems in Central Java, Indonesia. Biodiversitas 27 (1): d270103. https://doi.org/10.13057/biodiv/d270103. Black rice (Oryza sativa) is a high-value functional food; however, its productivity remains low due to limited adaptability and narrow genetic diversity. This study aimed to evaluate the yield stability and adaptability of two selected black rice mutant lines compared to three check varieties across multiple dry-season agroecosystems in Central Java, Indonesia. A multilocation trial was conducted at four sites in Klaten and Boyolali during the 2024 dry season using a randomized complete block design with five replications. The genetic materials consisted of two promising mutant lines (51 and 52) and three check varieties (Sembada, Jeliteng, and Cempo Ireng). Analyses included ANOVA, estimation of genetic parameters (GCV, PCV, and heritability), and stability-adaptability assessments using AMMI and GGE biplot models. There were significant genotype effects (p<0.01) on all major traits, with Genotype × Environment (G×E) interactions were significant for most growth traits but not for yield per plot and per hectare. The promising line 52 exhibited the highest mean yield (7.68 t ha⁻¹), significantly higher than the promising line 51 (6.43 t ha⁻¹) and the check varieties (≤5.98 t ha⁻¹). Broad-sense heritability estimates were greater than 50% for most yield-related traits, indicating strong genetic control. The promising line 52 exhibited the highest productivity with specific adaptation to certain environments, whereas promising line 51 demonstrated moderate yield performance with broader stability and adaptability. These findings confirm the presence of G×E interactions influencing yield expression. Therefore, multi-season testing is required to obtain a more comprehensive evaluation of yield stability and adaptability under varying climatic conditions, ensuring the selection of superior black rice genotypes that are high-yielding, stable, and resilient to seasonal fluctuations.